2006
DOI: 10.1007/s00259-006-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of HER2-expressing tumours using a synthetic Affibody molecule containing the 99mTc-chelating mercaptoacetyl-glycyl-glycyl-glycyl (MAG3) sequence

Abstract: Incorporation of a mercaptoacetyl-containing chelating sequence during chemical synthesis enabled site-specific (99m)Tc labelling of the Z(HER2:342) Affibody molecule with preserved targeting capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 46 publications
1
103
0
Order By: Relevance
“…Apparently, incorporation of the triglutamyl spacer reduced the on-rate of the binding, which caused increase of the dissociation constant from 49 pM for FBO-PEP4313 to 180 pM for FBO-E 3 -PEP4313. This was not entirely unexpected, as N-terminal modification has earlier caused some modulation of affinity of Affibody molecules 34,38 . However, our recent study 39 Reduction of the renal uptake was an interesting effect of the spacer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Apparently, incorporation of the triglutamyl spacer reduced the on-rate of the binding, which caused increase of the dissociation constant from 49 pM for FBO-PEP4313 to 180 pM for FBO-E 3 -PEP4313. This was not entirely unexpected, as N-terminal modification has earlier caused some modulation of affinity of Affibody molecules 34,38 . However, our recent study 39 Reduction of the renal uptake was an interesting effect of the spacer.…”
Section: Discussionmentioning
confidence: 98%
“…Binding specificity and cellular processing of 18 F-FBO-E 3 -PEP4313 was studied using HER2-expressing ovarian carcinoma SKOV-3 cells (1.6x10 6 receptors/cells 38 ). 18 F-FBO-E 3 -PEP4313 at a protein concentrations of 270 pM was added to 6 dishes (10 6 cells/ dish).…”
Section: In Vitro Binding Specificity and Cellular Processingmentioning
confidence: 99%
“…For use in comparative biodistribution experiments, the synthetic Affibody molecule maGGG-Z HER2:342 was labeled with 99m Tc according to a previously published method (22). A recombinant Affibody molecule (Z HER2:342 ) was indirectly radioiodinated using a succinimidyl ester of p-iodobenzoate according to Orlova and co-workers (18) and designated as 125 I-PIB-Z HER2:342 .…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4 presents the biodistribution of the labeled conjugates in normal mice 4 h pi. For comparison, we also included the previously described 99m Tc-maGGG-Z HER2:342 (22) in the study. The biodistribution studies showed rapid renal excretion with about 50% IA/g trapped in the kidneys for 99m Tc-CGG-and CGGG-Z HER2:342 (both directly and indirectly labeled) 4 h pi, while the 99m Tc-maGGG-Z HER2:342 displayed much lower uptake, less than 7% IA/g.…”
Section: Peptidementioning
confidence: 99%
See 1 more Smart Citation